Factors that affect employee retention in Wisma Felcra Berhad / Nur E’zzati Aqila Khair - Khair, Nur E’zzati Aqila (Faculty of Business and Management, 2019)
Employees are an organization’s most valuable assets. Their importance for organizations is not only the need to attract the best talent, but also the need to retain them for the long term. This paper focused to identify factors that affect employee retention. This research examined the following key factors to employee retention closely: training and development, compensation and work-life balance. The problem statement for this study, such as the cost loss associate with turnover for organization, employees feel stress to cope with the new thing, feel discomfort and displeasure with their work and employee will generate negative outcome in organization. Besides that, for the total population in this study consist 588 employees. Therefore, the researcher had distributed 265 questionnaires to the 265 of the respondents. In this case, it because the researcher believe that to reach 265 number of respondents is possible to do so and only 225 valid questionnaires been return back. The data collected was processed using Statistical Package for Social Science (SPSS) version 20. The data were analyzed using Descriptive, Pearson correlation and multiple regressions analysis. Therefore, the results from this study revealed that there is a positive and significant relationship between training and development and work-life balance and employee retention. However, the relationship between compensation and employee retention was found negative and not significant. The results also indicated that there are many other factors that can contribute to employee retention which are not included in this research. The sample study is only limited to the employees that are working at Wisma FELCRA Berhad.